2017
DOI: 10.1007/s11682-016-9656-9
|View full text |Cite|
|
Sign up to set email alerts
|

Considering total intracranial volume and other nuisance variables in brain voxel based morphometry in idiopathic PD

Abstract: Voxel-based morphometry (VBM) studies of Parkinson's disease (PD), have yielded mixed results, possibly due to several studies not accounting for common nuisance variables (age, sex, and total intracranial volume [TICV]). TICV is particularly important because there is evidence for larger TICV in PD. We explored the influence of these covariates on VBM by 1) comparing PD patients and controls before adding covariates, after adding age and sex, and after adding age, sex and TICV, and 2) by comparing controls sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 46 publications
5
35
0
Order By: Relevance
“…The ranges of the WMH loads found in this study for both control and de novo PD populations (mean value of 7 CCs = 0.37% of the total intracranial volume) were similar to values reported in other normal aging studies, suggesting that similar trends of decline can be expected in such populations as well ( De Marco et al, 2017 ; Huang et al, 2018 ; Wiseman et al, n.d. ; Zhang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ranges of the WMH loads found in this study for both control and de novo PD populations (mean value of 7 CCs = 0.37% of the total intracranial volume) were similar to values reported in other normal aging studies, suggesting that similar trends of decline can be expected in such populations as well ( De Marco et al, 2017 ; Huang et al, 2018 ; Wiseman et al, n.d. ; Zhang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, normal aging is shown to be more confined to the frontal circuit with the coexistence of disruptions in the genu and anterior cingulum ( 53 ). There are also several reports of the centrality of lower integrity of CC and cingulum in relation with poorer cognition and transition to demented state in patients with PD ( 54 58 ). Of note, the prefrontal white matter is the most consistently described region in PD ( 33 ), considering the executive dysfunction as the main cognitive disturbance in this neurodegenerative disorder ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that phantom sensations in general [ 119 ] and PLP in particular are associated with impairments in the body schema, describing a flexible central representation of body posture that is needed for action. Since mental rotation of body parts involves motor imagery processes [ 120 ], and since the associated neural mechanisms are different in amputees with PLP compared to amputees without PLP [ 121 ], these results highlight the impaired mentalization of motor execution specifically for painful phantom limbs. Consequently, it has been suggested that the central body representation itself should be a target of therapeutic approaches [ 122 ], and thus, novel treatments aim at normalizing the underlying processes [ 123 130 ].…”
Section: Changes In Body Perception and Their Relationship To Plpmentioning
confidence: 99%